2021
DOI: 10.34172/aim.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of Launching Mother’s Milk Bank in Neonatal Intensive Care Unit: A Retrospective Study

Abstract: Background: The WHO and UNICEF have suggested pasteurized donor milk (PDM) as the best alternative for infants who do not receive enough milk from their mothers. Objective: This study aimed to assess the short-term outcomes of launching the first mother's milk bank in North-West of Iran. Methods: The present retrospective study included 366 premature infants (181 pre-launch and 185 post-launch) who were hospitalized in Al-Zahra Hospital of Tabriz, Iran. The study included infants with birth weight ˂2000 g and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Additionally, most participants believed that HMBs should be located near NICUs. Retrospective studies by Hosseini et al (2021) found that the frequencies of necrotizing enterocolitis (NEC) and retinopathy of prematurity (ROP), as well as mortality rates in premature infants, decreased after a HMB was launched in an NICU in Iran. Jahan et al (2022) and Gürel & Erenel (2020) reported that HMBs near NICUs are important for meeting the needs of premature and low-weight infants for human milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, most participants believed that HMBs should be located near NICUs. Retrospective studies by Hosseini et al (2021) found that the frequencies of necrotizing enterocolitis (NEC) and retinopathy of prematurity (ROP), as well as mortality rates in premature infants, decreased after a HMB was launched in an NICU in Iran. Jahan et al (2022) and Gürel & Erenel (2020) reported that HMBs near NICUs are important for meeting the needs of premature and low-weight infants for human milk.…”
Section: Discussionmentioning
confidence: 99%
“…Human milk can be safely stored in HMBs after undergoing rigorous testing and pasteurization procedures. The provision of human milk from these banks serves as an important alternative for the treatment and care of preterm and low birth weight infants (Fonseca et al, 2021; Hosseini et al, 2021; Quigley et al, 2019; Sánchez Luna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The accessibility of a human milk bank (HMB) could be an important factor associated with initiating ETF. The benefits of implementation of an HMB in NICUs have been reported by several studies ( Table S1 ) [ 22 , 23 , 24 , 25 , 26 ]. To date, seldom studies report the influence on growth outcome of these very preterm infants after the implementation of an HMB in NICUs.…”
Section: Introductionmentioning
confidence: 92%
“…These children are forbidden to marry each other (13). However, the first human milk bank in Iran was established in July 2016 at Al-Zahra Teaching Hospital in Tabriz (14).…”
Section: Introductionmentioning
confidence: 99%